Comparison of Diagnostic Accuracy of Magnetic Resonance Imaging and Transient Elastography Fibro Scan for Detecting Liver Fibrosis - Ramsha Shahzeen, Zaeem Sibtain, Niaz Ahmed, Muhammad Affan Qaiser, Nazish Butt, Ghulam Muhammad (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: Diagnosing liver fibrosis without resorting to invasive surgery is in high demand but underserved. The focus of this study is on the diagnostic accuracy of MRI and the transient elastography fibro scan for liver fibrosis. Methodology: After the ethical approval from institute review board, sixty patients with liver fibrosis were selected by random sampling technique underwent multiparametric MR, transesophageal echocardiography (TE), and blood testing in this single-center cross-sectional study. Noninvasive treatment alternatives were weighed against histological information including stage and grade (such as MR fat and iron content). The diagnostic accuracy of each method for F3 and F4 hepatic fibrosis, as well as for advanced fibrosis, was evaluated using ROC curve analysis. Each technique was evaluated based on its accuracy (F3–F4). Results: Magnetic resonance elastography was used to find significant correlations between fibrosis stage and collagen content (r = 0.66; P = 0.001), as well as between inflammatory grade and collagen content (r = 0.53; P = 0.036). The MRE, TE, DCE-MRI, DWI, and APRI all had AUCs of 0.78 or above, while the AUC for identifying advanced fibrosis was 0.71. Advanced fibrosis AUC values were between 0.94 and 0.77, 0.79 and 0.79, and 0.70 and 0.70. (F3–F4). Practical implication: This study will to determine which diagnostic technique is better suited to accurately diagnose the liver fibrosis patients. Conclusion: The strongest correlation was seen between histological markers and MRI. The ability of magnetic resonance imaging to detect advanced liver fibrosis and cirrhosis was also superior to that of transient elastography fibro scans. Keywords: MRI, Liver fibrosis, diagnostic accuracy, transient elastography fibro scan